PENTINGNYA KETERAMPILAN MANAJEMEN USAHA PADA HOME INDUSTRY TAPE SINGKONG DI KECAMATAN PAKUSARI KABUPATEN JEMBER - Diah Yulisetiarini; Susanti Prasetyaningtyas; Sudarsih Sudarsih; Bambang Irawan (As-Sidanah, 2022)
The business of making cassava tape has a positive impact, both on entrepreneurs and the local community. For entrepreneurs, the economic impact of this business is to increase their income. In addition, the operation of a labor-intensive cassava tape business will help absorb labor for the local community. Work productivity of employees is very important so the skills of employees in the home industry of cassava tape need to be continuously improved. The purpose of this study was to determine how much influence work skills have on the productivity of making cassava tape in the home industry in Pakusari District, Jember Regency. This research method uses quantitative description. The results of this study indicate that the work skills of employees have a significant positive effect on the productivity of making cassava tape in the home industry in Pakusari District, Jember Regency.